Sorgo grão e desempenho de codornas ao abate - Moraes, Cíntia Amaral (2014)
This study aimed to compare four levels of ground grain sorghum as an energy source in the diet of Japanese quails to court, evaluating the growth performance, carcass yield and cuts and the chemical composition of some cuts. In total, 1200 Japanese quail (Coturnix coturnix japonica), females with a day old, were distributed according to a completely randomized design consisting of four treatments and six replicates each, as follows: 0%, 40%, 60%, sorghum 100% in the two phases (start, a growth 21 days and from 22 to 42 days of age). The variables analyzed were weight gain; feed conversion; mortality; eviscerated carcass yield and cuts (full chest-, thighs / drumsticks); chemical composition of breast and drumstick / thigh. The performance variables were submitted to the Anderson-Darling test and the nonparametric Kruskal-Wallis. Variables yield and carcass composition were subjected to the Anderson-Darling test and the means were compared by Tukey test and Scott-Knott. There were no significant differences in performance variables, yield and composition of cuts. We conclude sorghum can be used as an ingredient in the nutrition of Japanese quail to cut without sacrificing performance (feed conversion, weight gain and mortality) as well as the yield of cuts (drumstick / thigh and breast) and housing and also qualitative characteristics of the cuts (drumstick / thigh and chest).